The relative age effect in the European Weightlifting Championships 2015-2019 (male and female) - Isik, B.; Erdagi, K. (Medicina dello Sport, 2022)
BACKGROUND In terms of sporting activities, the relative age effect means the possible advantages of participation and performance of athletes who were born closer to the beginning of the year of selection corresponding to other athletes within the same age category. The aim of this study is to investigate the relative age effect on male and female athletes Olympic weightlifting athletes that participated in the European Weightlifting Championships from 2015 to 2019. Moreover, the study also aims to find out the birthdate quarter of elite athletes who ranked in the first three medalists in the championships.